PROBLEM OF CARIES IN PRIMARY TEETH AT CHILDREN (LITERATURE REVIEW) - L.F. Kaskova; N.A. Morhun; N.V. Yanko; I.Yu. Vashchenko; O.V. Khmil; O.Yu. Andryanova (Український стоматологічний альманах)
The aim of the study is to analyze literature sources on the prevalence of caries in primary teeth among children worldwide, the factors leading to the development of this pathology, and the possibilities for its prevention.